In vivo Imaging of Retina and Choroid in Guinea Pigs - Dong, Li; Li, Yi Fan; Jiang, Xue; Lan, Yin Jun; Shao, Lei; Jonas, Jost B.; Wei, Wen Bin (Frontiers in Medicine, 2021)
Purpose: To evaluate the feasibility of in vivo imaging of the retina and choroid using spectral domain optical coherence tomography (OCT) in guinea pigs. Methods: The study included 19 pigmented guinea pigs (age:3-4 weeks) which underwent sonographic axial length measurements and OCT imaging. At study end, the animals were sacrificed and histomorphometric examinations of the retina and choroid were performed. We assessed the reproducibility of the OCT measurements and compared in vivo images to histomorphometric data. Results: The mean thickness of the retina and choroid near the optic nerve head was 175.6±25.8 μm and 63.4±16.5 μm, respectively. The mean Bruch’s membrane opening (BMO) diameter was 831±121 μm. A high correlation was found for the intra-observer measurements of retinal thickness (intraclass correlation coefficient (ICC)=0.92,95% CI:0.86-0.96;P<0.001), choroidal thickness (ICC=0.92,95% CI:0.86-0.96;P<0.001), and BMO diameter (ICC=0.92,95% CI:0.86-0.96;P<0.001). High agreement was also present for the inter-observer reproducibility of the measurements of retinal thickness (Pearson correlation coefficient (R)=0.98;P<0.001), choroidal thickness (R=0.96;P<0.001), and BMO diameter (R=0.98;P<0.001). The Bland-Altman plots showed that 2.6% (1/38), 5.3% (2/38), and 7.9% (3/38) of the points for the measurement of retinal thickness, choroidal thickness and BMO diameter, respectively, were located outside of the 95% limits of agreement. The OCT-based thickness measurements of retina and choroid were significantly higher than those measured by histomorphometry (both P-values<0.01). Conclusion: Our study showed the feasibility of OCT for in vivo morphometric imaging of the retina and choroid in guinea pigs with an acceptable intra-observer repeatability and inter-observer reproducibility.